Development of the transfemoral prosthesis for swimming focused on ankle joint motion - Nakashima, M.; Suzuki, S.; Ono, A.; Nakamura, T. (Journal of Biomechanical Science and Engineering, 2013)
The objective of this study was to develop a prototype of transfemoral prosthesis for swimming focused on the ankle joint motion. This prosthesis has (i) an ankle joint which provides appropriate foot motion, (ii) the capability of walking on land by the poolside, (iii) and a foot whose appearance is sufficiently similar to an actual one. In order to confirm the validity of the developed prosthesis, a swimming experiment, in which a subject swimmer swam in a pool with the developed prosthesis attached, was conducted. The joint angles of the lower limbs were measured and an evaluation with questionnaires was performed. The validity of the proposed prosthesis was experimentally confirmed since the movable ankle joint with an appropriate spring brought a large foot motion, yielding a better swimming performance and more comfort to the swimmer. In addition to the experiment, the simulation of the swimming movement with the prosthesis was conducted. Through the simulation, the general validity of the developed prosthesis was confirmed since the simulation's result exhibited the same tendency as the experiment, in which a spring constant that was too large for the extension spring brought worse swimming performance.